Simulation of electromagnetic field (EM) focusing capability on biological tissue through the application of C-type excitation coil screen - Zulkarnay, Zakaria; Noor Alia, Mohd Zain; Azian Azamimi, Abdullah; Sofi, Yahya; Ruzairi, Abdul Rahim, Prof. Dr.; Muhammad Saiful Badri, Mansor; Abdul Rahim, Mohd Disar (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/